Morphological screening of early segregating generations of brinjal (Solanum melongena) for resistance against brinjal shoot and fruit borer - ANKIT KUMAR UPADHYAY; JIJI JOSEPH; ASISH I EDAKKALATHUR; BERIN PATHROSE; BEENA C (The Indian Journal of Agricultural Sciences, 2024)
Brinjal (Solanum melongena L.), commonly referred as eggplant, represents a globally cultivated vegetable crop highly susceptible to numerous pests and diseases. The brinjal shoot and fruit borer (BSFB) emerges as a particularly detrimental pest, causing potential losses ranging from 70–92%. The absence of effective biological control necessitates extensive research to develop brinjal varieties resistant to BSFB as they will have the potential to furnish an eco-friendly, economically viable, and sustainable strategy for pest management in brinjal cultivation. The present study was carried out during 2022 and 2023 at Kerala Agricultural University, Vellanikkara, Thrissur, Kerala to identify superior lines exhibiting resistance to shoot and fruit borer from early segregating generations (F3 and F4) of the cross Ponni × Vengeri which was moderately resistant to BSFB. Both pedigree and single seed descent (SSD) methodologies were employed, revealing considerable variation in qualitative and quantitative traits, encompassing mean, range, and genetic parameters (GCV, PCV, H2, GA, GAM, skewness, and kurtosis) across successive generations. The persistence of trait variation in the subsequent generation was ensured from the absence of selection during the single-seed descent method. Superior lines, namely 1.2.18.8, 1.2.10.7 and 1.3.10.7 were identified through the pedigree method, while 1.3.11.2, 1.4.13.2 and 1.10.16.4 emerged as superior lines through SSD method, having resistance against BSFB.